Gendering the Interview: Feminist Reflections on Gender as Performance in Research - Golombisky, Kim (Women's studies in communication, 2006)
This reflexive essay argues that gender is co-performed but that researchers have greater responsibility for gender performances during research. In the present case, the author began an oral history project with a masculine definition of history, cast narrators using gendered criteria, directed gendered communication performances during interviewing, and elicited narratives via gendered categories. Understanding gender as co-performative encourages researchers to study the communication of gender and to consider the ways they may gender their work.